POLITICAL ECONOMY OF DEVELOPMENT AND ENVIRONMENT IN MODERN INDIA - Saravanan, Velayutham ([S.l.] : ROUTLEDGE, 2023)
This book captures the complexities of both development and environment, from the political economy point of view, to offer a broad economic and environmental history of post-independence India. It analyses the various components of constitutional provisions, policies, programmes and ecology protection measures during the post-independence period, that is, 1947-2020. The author also investigates India's land and forest policies of the 21st century: Fair Compensation of Land Acquisition, Rehabilitation and Resettlement Act 2013 and the Scheduled Tribes and Other Traditional Forest Dwellers (Recognition of Forest Rights) Act 2006, which pose a great threat to ecology and the environment. The volume argues how, on one hand, the development agenda has undermined the environmental components for the first three decades of independence and, on the other hand, how the popular vote bank politics further has aggravated the issues related to environment in India. This book is an essential interdisciplinary resource for scholars and researchers of history, economic history, environmental studies, environmental history, Indian history and development studies.
Keywords: HISTORY / Asia / India & South Asia; HISTORY / General; SOCIAL SCIENCE / General; Human ecology -- India -- History -- 20th century; India -- Economic conditions -- 1947-; India -- Politics and government -- 1947-